2005
DOI: 10.4141/s04-044
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial biomass, functional diversity and crop yields following application of cattle manure, hog manure and inorganic fertilizers

Abstract: Soil microbial biomass, functional diversity and crop yields following application of cattle manure, hog manure and inorganic fertilizers. . Soil biological properties can be significantly impacted by land management. Cattle manure, hog manure or inorganic fertilizers were applied annually or triennially in field trials conducted at two sites over 3 yr. A control treatment without manure or fertilizer was also included. Canola (Brassica napus) was grown in year 1, hulless barley (Hordeum vulgare) in year 2, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
6
17
0
Order By: Relevance
“…The lower d 15 N of grain (+2.2 to +4.1&) than that of the N source (+7.9& for total N, +9.9& for NH 4 + , and +16.6& for NO 3 ) ) in the cattle manure treatment in combination with the non-significant effect of cattle manure application on grain N concentrations (Figure 1a), clearly shows the low N availability of solid cattle manure where most N was present as organic N (Table 2). Lupwayi et al (2005) also reported that the hog manure treatment resulted in higher nutrient (N, P, and K) contents in crop tissues than the cattle manure treatment in the same experimental plots as in this study. This implies that in the cattle manure treatment, a greater proportion of the crop N requirement was met by native soil N supply through mineralization, as the d 15 N (+4.1&) of total soil-N was lower than that (+7.9&) of the cattle manure applied.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The lower d 15 N of grain (+2.2 to +4.1&) than that of the N source (+7.9& for total N, +9.9& for NH 4 + , and +16.6& for NO 3 ) ) in the cattle manure treatment in combination with the non-significant effect of cattle manure application on grain N concentrations (Figure 1a), clearly shows the low N availability of solid cattle manure where most N was present as organic N (Table 2). Lupwayi et al (2005) also reported that the hog manure treatment resulted in higher nutrient (N, P, and K) contents in crop tissues than the cattle manure treatment in the same experimental plots as in this study. This implies that in the cattle manure treatment, a greater proportion of the crop N requirement was met by native soil N supply through mineralization, as the d 15 N (+4.1&) of total soil-N was lower than that (+7.9&) of the cattle manure applied.…”
Section: Discussionsupporting
confidence: 62%
“…The size of each plot was 3.7 m  15.2 m. Details of the study site and experimental design have been described in Lupwayi et al (2005). From the 18 treatments, we selected four treatments: (1) control without organic manure or chemical fertilizer applied (Control), (2) annual broadcast-application of hog manure (liquid) at N requirement level (Hog), (3) annual broadcastapplication of cattle manure (solid) at N requirement level (Cattle), and (4) annual application of chemical N-fertilizer (a combination of urea and ammonium phosphate) at N requirement level (Table 1) to meet crop N requirements according to soil test recommendations.…”
Section: Study Site and Field Experimentsmentioning
confidence: 99%
“…However, the difference in plant d 15 N at harvest between the synthetic and organic fertilizers was <4% in Bateman et al (2005), <2% in Georgi et al (2005), and <2% in Choi et al (2002). This pattern might have reflected differences in the availability of N in the organic input; i.e., when the organic input was in the liquid form, as was in our study and in the fertigation study of Nakano et al (2003), the difference in plant d 15 N between organic and inorganic inputs became greater than when the organic input was in the solid form, which usually have lower N availabilities than the liquid type of organic fertilizers (Lupwayi et al 2005). In a 4-year crop rotation (canola-barleywheat-canola) experiment conducted in northwestern Alberta, Canada, Choi et al (2006) also found that d 15 N in grain was greater after liquid hog manure application (d 15 N in grain ranged from +5.6 to +8.4%) than after solid cattle manure application (d 15 N in grain ranged from +2.2 to +4.1%) in spite of the higher d 15 N of N in cattle (+7.9%) than in hog manure (+5.1%).…”
Section: Plant Growth and N Uptakementioning
confidence: 49%
“…(1 in barley rhizosphere of a similar soil (Lupwayi et al 2005). Wood ash and lime have been shown to increase soil microbial biomass and activity in other studies (Weber et al 1985;Bezdicek et al 2003;Fuentes et al 2006).…”
Section: The Levels Of Mbc (3000 Mg Kgmentioning
confidence: 75%